Thermodynamic modelling of cryo compressed hydrogen storage tanks for trucks - Lokesh, Surya Prakash Avaragere; Ranjbar, Artin (My University, 2022)
Currently today’s transportation is either by conventional ICE driven vehicles, fully electric vehicle or hybrid vehicle. Based on environmental impact with increasing concentration of greenhouse gases in the atmosphere such as Carbon dioxide and nitrogen dioxides emerged partly as a bi-product from combustion, there has been a rising initiative to electrify transportation and cut down on tail pipe emissions. However, driving range in electrified vehicles may be short for long haul truck ap plications and in general, transition towards electrification has been too quick for a proper charging infrastructure to be implemented. Fuel Cell driven vehicles with hydrogen is a concept that has been initiated as an alternative fuel which during energy conversion in fuel cells will produce water as the only bi-product and with higher possibilities to achieve longer driving range than battery electric vehicles. In this thesis, study is focused on storage of hydrogen for automotive applications. Simulation of different truck operations that could possibly take place in a real life to observe how the truck operations would affect the overall storage performance in terms of thermal aspects such as pressure, temperature and density in the tank. Key state properties of storage tank in this study is fill density of hydrogen storage, boil-off losses and external heat required during hydrogen consumption. Initial tank temperature and pressure, fuel temperature and truck operation are the parameters affecting the state properties. Results from simulation in form of plots will help to visualise the evolution of state properties with change in mentioned parameters. Simulation is run with the help of GT SUITE by Gamma Technologies, which has a high computation power with predefined library of information of many fluids with a possibility to run simulations for hydrogen storage with the latest version of software.
Keywords: eywords: Fuel cell, hydrogen storage, cryogenic storage, cryo-compressed hydrogen, fill density, GT SUITE